Analysis of Factors that Influence Beginning Teachers' Perception of their Instructional Competency. Issue 1 (January 2014) - Chong, Sylvia; Loh, Wai Mun; Mak, Xueling Mabelene
Literature concerning teacher quality indicates that there is a core body of knowledge and skills that a teacher must be equipped with to develop competencies of effective teaching. Beginning teachers (n = 3, 353; 1–3 teaching years) participated in an online quality evaluation project at the National Institute of Education, Singapore. Factors underlying beginning teachers' perceptions of their teaching competencies were explored. First, the tool proved to be a reliable and valid measure. Second, analysis focused on a hypothesized path model of how the factors interact and contribute to beginning teachers' preparedness to teach. Possible implications are presented and discussed.